Identification and characterization of circulating and adipose tissue infiltrated CD20+T cells from subjects with obesity that undergo bariatric surgery - Pinho, Aryane Cruz Oliveira; Barbosa, Pedro; Lazaro, André; Tralhão, José G.; Pereira, Maria João; Paiva, Artur; Laranjeira, Paula; Carvalho, Eugenia (Immunology letters, 2024)
•Circulating CD20+T cells correlate with adiposity and cardiometabolic risk markers.•CD20+T cells infiltrating adipose tissue display IFN-γ-producing Th1 phenotype.•CD20+T cells may play a role in adipose tissue inflammation during obesity.•Bariatric surgery reduces some proinflammatory activity parameters of CD20+T cells, namely the levels of circulating CD20+ Th1 cells.•Interestingly, bariatric surgery induces a slight decrease PD-1 expression in CD20+T cells. T cells play critical roles in adipose tissue (AT) inflammation. The role of CD20+T cell in AT dysfunction and their contributing to insulin resistance (IR) and type 2 diabetes progression, is not known. The aim was to characterize CD20+T cells in omental (OAT), subcutaneous (SAT) and peripheral blood (PB) from subjects with obesity (OB, n = 42), by flow cytometry. Eight subjects were evaluated before (T1) and 12 months post (T2) bariatric/metabolic surgery (BMS). PB from subjects without obesity (nOB, n = 12) was also collected. Higher percentage of CD20+T cells was observed in OAT, compared to PB or SAT, in OB-T1. CD20 expression by PB CD4+T cells was inversely correlated with adiposity markers, while follicular-like CD20+T cells were positively correlated with impaired glucose tolerance (increased HbA1c). Notably, among OB-T1, IR establishment was marked by a lower percentage and absolute number of PB CD20+T cells, compared nOB. Obesity was associated with higher percentage of activated CD20+T cells; however, OAT-infiltrated CD20+T cells from OB-T1 with diabetes displayed the lowest activation. CD20+T cells infiltrating OAT from OB-T1 displayed a phenotype towards IFN-γ-producing Th1 and Tc1 cells. After BMS, the percentage of PB CD4+CD20+T cells increased, with reduced Th1 and increased Th17 phenotype. Whereas in OAT the percentage of CD20+T cells with Th1/17 and Tc1/17 phenotypes increased. Interestingly, OAT from OB pre/post BMS maintained higher frequency of effector memory CD20+T cells. In conclusion, CD20+T cells may play a prominent role in obesity-related AT inflammation.